Electrochemical devices and electronic devices
By using a negative electrode sheet of silicon-based material and an electrolyte of specific composition in lithium-ion batteries, the problem of poor circulation performance of lithium-ion batteries is solved, and stronger reduction resistance and better circulation performance are achieved.
Patent Information
- Application Number
- CN202280003781.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-01-26
AI Technical Summary
In existing lithium-ion batteries, silicon-based active materials expand and contract during circulation, resulting in rupture of the anode SEI film and consumption of electrolyte, thereby reducing the cycling performance of the battery.
A negative electrode sheet containing a silicon-based material and an electrolyte with a specific composition are used. The electrolyte contains fluorobenzene compound or fluoroether compound, a phosphate ester substance and a lithium salt. The mass ratio of the second substance to the third substance is controlled at 0.8≤Y≤4 to form a high-quality SEI film and improve the interface repair ability.
By using this electrochemical device, the circulation performance of lithium-ion batteries is significantly improved, the oxidation and decomposition of the electrolyte on the negative electrode is reduced, the reduction resistance of the negative electrode is enhanced, and rapid SEI film repair is achieved.
Smart Images

Figure BDA0003911230210000011 
Figure BDA0003911230210000041 
Figure BDA0003911230210000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Silicon is considered to be the most likely negative electrode material to replace graphite as a lithium-ion battery due to its high capacity and abundant reserves. However, currently commercial lithium-ion batteries mainly use traditional graphite as the negative electrode, because silicon-based active materials continue to expand and contract during the cycle, causing the rupture of the anode SEI film and the continuous consumption of the electrolyte, resulting in the deterioration of the cycle performance of lithium-ion batteries. Summary of the invention
[0003] In view of the problems existing in the background technology, the purpose of the present application is to provide an electrochemical device and an electronic device.
[0004] In order to achieve the above-mentioned purpose, the present application provides an electrochemical device, including a negative electrode plate and an electrolyte, wherein the negative electrode plate contains a negative electrode active material, and the negative electrode active material contains a silicon-based material; the electrolyte contains a first substance, a second substance and a third substance; the first substance is selected from a fluorobenzene compound or a fluoroether compound; the second substance is selected from at least one of phosphate, phosphite, carbonate, carboxylate, ether or sulfone; the third substance is a lithium salt; based on the mass of the electrolyte, the mass ratio of the second substance to the third substance is Y, and the range of Y is: 0.8≤Y≤4.
[0005] In some embodiments, the fluorobenzene compound is selected from at least one of fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene or hexafluorobenzene.
[0006] In some embodiments, the structural formula of the fluoroether compound is the compound shown in Formula 1
[0007]
[0008] wherein R1 and R2 are independently selected from substituted or unsubstituted C 1-12 Alkyl, C 1-12 Alkoxy; wherein, when substituted, the substituent is fluorine, and there are at least 4 fluorines in Formula 1.
[0009] In some embodiments, the fluoroether compound is selected from methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,1,2,2-pentafluoro-3-(trifluoromethoxy)propane, 1,1,1,2,2,3,3-heptafluoro-3-methoxypropane, ethyl 1,1,2,3,3,3-hexafluoropropyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,1,2,3,3-hexafluoro-3-methoxypropane, 2,2,3,3,3-pentafluoropropyl-1, At least one of 1,2,2-tetrafluoroethyl ester, methyl 2,2,3,3,3-pentafluoropropyl ether, 2,2,3,3-tetrafluoro-1-methoxypropane, 2,2,3,3,3-pentafluoropropyl difluoromethyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 4-(difluoromethoxy)-1,1,1,2,3,3-hexafluorobutane, 2H-hexafluoropropyl 2,2,3,3-tetrafluoroether or 1-(1,1,2,2-tetrafluoroethoxy)butane.
[0010] In some embodiments, the mass ratio of the first substance to the electrolyte is A%, and 15≤A≤80.
[0011] In some embodiments, the second substance is selected from at least one of the following substances:
[0012] Triethyl phosphite, trimethyl phosphite, triethyl phosphate, trimethyl phosphate, tripropyl phosphate, triphenyl phosphate, tris(trifluoroethyl) phosphate, tris(trimethylsilyl) phosphate, trimethylsilyl phosphite,
[0013] Bis(2,2,2-trifluoroethyl) carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dipropyl carbonate, methylpropyl carbonate, pentafluoropropyl ethylene carbonate, methyl trifluoroethyl carbonate, trifluoromethyl ethylene carbonate,
[0014] Propyl propionate, ethyl propionate, ethyl acetate, ethyl formate, methyl acetate, propyl acetate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl propionate, methyl trifluoropropionate,
[0015] Ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, 1,3-dioxane, 1,4-dioxane, ethylene glycol formic acid ethyl ether, diethoxymethane, 1,3-dimethoxypropane, 1,1,3,3-tetraethoxypropane, 18-crown-6, 12-crown-4, 15-crown-5, cyclopentane, dimethyl sulfone.
[0016] In some embodiments, the third substance is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorooxalatoborate), or lithium 4,5-dicyano-2-(trifluoromethyl)imidazole.
[0017] In some embodiments, the electrolyte further comprises an additive; the additive is at least selected from one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1,4-butane sultone, 2,4-butane sultone, succinonitrile, adiponitrile, trans-butene dinitrile, glutaronitrile, 1,3,6-hexane trinitrile, 1,2,3-tris(2-cyano)propane or hexylenonitrile. The mass proportion of the additive in the electrolyte is B%, and 0.5≤B≤30.
[0018] In some embodiments, based on the total weight of the negative electrode active material, the mass percentage of the silicon-based material is a%, and 10≤a≤90.
[0019] In some embodiments, a protective layer is provided on the surface of the silicon-based material particles. The protective layer is selected from graphite carbon material and / or functional oxide;
[0020] The chemical formula of the functional oxide is Me m O n , wherein Me includes at least one of Al, silicon, Mn, V, Cr, Co or Zr, m is 1 to 2, and n is 1 to 3.
[0021] In some embodiments, the present application also provides an electronic device, which includes the above-mentioned electrochemical device.
[0022] The present application at least includes the following beneficial effects:
[0023] In this application, silicon-based materials are applied to the negative electrode to provide a specific electrolyte with stronger reduction resistance at the negative electrode. When the SEI film at the negative electrode interface is broken, its reactivity at the negative electrode is weaker. At the same time, the SEI film at the interface can be repaired quickly, reducing the oxidative decomposition of the electrolyte at the negative electrode, so as to improve the cycle performance of the electrochemical device. DETAILED DESCRIPTION
[0024] The exemplary embodiments are described in detail below, but these exemplary embodiments can be implemented in different ways and should not be interpreted as being limited to the embodiments described in this application. On the contrary, the purpose of providing these embodiments is to make the disclosure of this application thorough and complete, and to fully convey the scope of this application to those skilled in the art.
[0025] (Electrochemical Device)
[0026] The electrochemical device may be a capacitor, a lithium ion battery, a sodium ion battery or a zinc ion battery, for example, a lithium ion capacitor, a lithium ion primary battery or a lithium ion secondary battery.
[0027] The electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.
[0028] [Electrolyte]
[0029] In some embodiments, the electrolyte contains a first substance, a second substance and a third substance. Adding the first substance, the second substance and the third substance to the electrolyte can significantly improve the cycle performance of the electrochemical device.
[0030] In some embodiments, the first substance is selected from fluorobenzene compounds or fluoroether compounds. To ensure a high concentration of lithium salt, the added fluoroether or fluorobenzene solvent can form an elastic organic SEI layer on the silicon negative electrode, and the film-forming effect of the two can effectively improve the cycle performance of the silicon anode battery.
[0031] In some embodiments, the second substance is selected from at least one of phosphates, phosphites, carbonates, carboxylates, ethers, or sulfones.
[0032] In some embodiments, the third substance is a lithium salt.
[0033] In some embodiments, based on the mass of the electrolyte, the mass ratio of the second substance to the third substance is Y, and the range of Y is: 0.8≤Y≤4. In the electrolyte, the mass ratio of the solvent to the lithium salt is controlled at 0.8-4, which can ensure a high concentration of the lithium salt. The lithium ion coordination at this time is inconsistent with the traditional electrolyte system. Due to the high concentration of the lithium salt, the anions of the lithium salt participate in the inner layer coordination of the lithium ions, and when the ion clusters reach the ruptured SEI surface, the anions quickly participate in the film formation of the SEI, and the SEI is repaired in a timely and high-quality manner.
[0034] In some embodiments, the fluorobenzene compound is selected from at least one of fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene or hexafluorobenzene.
[0035] In some embodiments, the structural formula of the fluoroether compound is the compound shown in Formula 1
[0036]
[0037] wherein R1 and R2 are independently selected from substituted or unsubstituted C 1-12 Alkyl, C 1-12 Alkoxy; wherein, when substituted, the substituent is fluorine, and there are at least 4 fluorines in Formula 1.
[0038] In some embodiments, the fluoroether compound is selected from methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,1,2,2-pentafluoro-3-(trifluoromethoxy)propane, 1,1,1,2,2,3,3-heptafluoro-3-methoxypropane, ethyl 1,1,2,3,3,3-hexafluoropropyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,1,2,3,3-hexafluoro-3-methoxypropane, 2,2,3,3,3-pentafluoropropyl-1, At least one of 1,2,2-tetrafluoroethyl ester, methyl 2,2,3,3,3-pentafluoropropyl ether, 2,2,3,3-tetrafluoro-1-methoxypropane, 2,2,3,3,3-pentafluoropropyl difluoromethyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 4-(difluoromethoxy)-1,1,1,2,3,3-hexafluorobutane, 2H-hexafluoropropyl 2,2,3,3-tetrafluoroether or 1-(1,1,2,2-tetrafluoroethoxy)butane.
[0039] In some embodiments, the mass ratio of the first substance to the electrolyte is A%, 15≤A≤80. When the mass ratio of the first substance is low, such as less than 15%, the content of the second substance or the third substance in the electrolyte is relatively high. When the content of the second substance is relatively high, the lithium salt content in the formed electrolyte system is relatively low, which affects the dissociation and adsorption of positive and negative lithium ions and the cycle performance of the electrochemical device. When the content of the third substance is relatively high, the viscosity of the electrolyte will increase, affecting the improvement of the battery cycle performance. When the mass ratio of the first substance is too high, such as higher than 80%, the content of the second substance or the third substance in the electrolyte is too low, which is not conducive to the conduction of ions in the electrolyte and affects the discharge capacity of the electrochemical device.
[0040] In some embodiments, the second substance is selected from at least one of the following substances:
[0041] Triethyl phosphite, trimethyl phosphite, triethyl phosphate, trimethyl phosphate, tripropyl phosphate, triphenyl phosphate, tris(trifluoroethyl) phosphate, tris(trimethylsilyl) phosphate, trimethylsilyl phosphite,
[0042] Bis(2,2,2-trifluoroethyl) carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dipropyl carbonate, methylpropyl carbonate, pentafluoropropyl ethylene carbonate, methyl trifluoroethyl carbonate, trifluoromethyl ethylene carbonate,
[0043] Propyl propionate, ethyl propionate, ethyl acetate, ethyl formate, methyl acetate, propyl acetate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl propionate, methyl trifluoropropionate,
[0044] Ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, 1,3-dioxane, 1,4-dioxane, ethylene glycol formic acid ethyl ether, diethoxymethane, 1,3-dimethoxypropane, 1,1,3,3-tetraethoxypropane, 18-crown-6, 12-crown-4, 15-crown-5,
[0045] Sulfolane, dimethyl sulfone.
[0046] In some embodiments, the third substance is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorooxalatoborate), or lithium 4,5-dicyano-2-(trifluoromethyl)imidazole.
[0047] In some embodiments, the electrolyte further comprises an additive; the additive is at least selected from one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1,4-butane sultone, 2,4-butane sultone, succinonitrile, adiponitrile, butadiene dinitrile, glutaronitrile, 1,3,6-hexanetrinitrile, 1,2,3-tris(2-cyano)propane or acetylene nitrile.
[0048] In some embodiments, the mass proportion of the additive in the electrolyte is B%, 0.5≤B≤30. When the content of the additive is too low, such as less than 0.5%, an effective and continuously protective interface layer cannot be formed at the interface, which is not conducive to the long cycle of the battery. When the content of the additive is too high, the viscosity of the electrolyte increases, affecting the conductivity of the electrolyte, and the interface impedance increases, affecting the cycle performance of the electrochemical device;
[0049] [Negative electrode]
[0050] The negative electrode sheet includes a negative electrode current collector and a negative electrode membrane.
[0051] In some embodiments, the negative electrode current collector is a metal, such as but not limited to copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0052] The negative electrode membrane is arranged on the surface of the negative electrode current collector and contains negative electrode active material.
[0053] In some embodiments, the negative electrode active material comprises a silicon-based material.
[0054] In some embodiments, based on the total weight of the negative electrode active material, the mass percentage of the silicon-based material is a%, and 10≤a≤90. The addition of silicon-based materials can significantly improve the volume energy density of the electrochemical device, but when the content of silicon-based materials is too high, such as higher than 90%, the negative electrode will have a large expansion deformation, resulting in electrical contact failure, affecting the cycle performance of the electrochemical device; when the content of silicon-based materials is too low, such as lower than 10%, the effect of improving the energy volume density of the electrochemical device is not significant, and the effect of improving the cycle performance of the electrochemical device is low.
[0055] In some embodiments, a protective layer is provided on the surface of the silicon-based material particles. The protective layer is selected from graphite carbon materials and / or functional oxides. After the protective layer is provided on the surface of the silicon-based material, the expansion of the silicon-based material can be suppressed, and the cycle stability of the battery can be further improved.
[0056] In some embodiments, the functional oxide has a chemical formula of Me m O n , wherein Me includes at least one of Al, silicon, Mn, V, Cr, Co or Zr, m is 1 to 2, and n is 1 to 3.
[0057] In some embodiments, the negative electrode membrane further comprises a negative electrode binder. In some embodiments, the negative electrode binder comprises at least one of difluoroethylene-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon.
[0058] In some embodiments, the method for preparing the negative electrode sheet is a method for preparing the negative electrode sheet that is well known in the art and can be used for an electrochemical device. In some embodiments, the negative electrode active material, the negative electrode binder, and the optional conductive material and thickener as needed are dissolved or dispersed in a solvent to form a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode collector, and then dried, rolled, and cut to obtain a negative electrode sheet. It should be noted that in the obtained negative electrode sheet, the portion containing the negative electrode active material on the surface of the negative electrode collector is a negative electrode film.
[0059] [Positive electrode]
[0060] The positive electrode sheet includes a positive electrode current collector and a positive electrode membrane.
[0061] The positive electrode current collector is a metal, such as but not limited to aluminum foil.
[0062] The positive electrode membrane is arranged on the surface of the positive electrode current collector. The positive electrode membrane contains a positive electrode active material. When the electrochemical device is a lithium ion battery: the positive electrode active material can be selected from lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, olivine structure lithium phosphate, etc., such as lithium cobalt oxide or lithium manganese oxide, but the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for lithium ion batteries can also be used.
[0063] In some embodiments, the method for preparing the positive electrode sheet is a method for preparing the positive electrode sheet that is well known in the art and can be used for electrochemical devices. In some embodiments, in the preparation of the positive electrode slurry, the positive electrode active material, the binder and the optional conductive material are added as needed and then dissolved or dispersed in a solvent to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector, then dried, rolled, and cut to obtain the positive electrode sheet. It is noted that in the obtained positive electrode sheet, the portion containing the positive electrode active material on the surface of the positive electrode collector is the positive electrode film.
[0064] [Isolation film]
[0065] In some embodiments, the isolation film is polyethylene, polypropylene, polyvinylidene fluoride or a multilayer composite film thereof.
[0066] In some embodiments, the isolation film is a single-layer isolation film or a multi-layer isolation film.
[0067] In some embodiments, the isolation film is coated with a coating. In some embodiments, the coating comprises at least one of an organic coating and an inorganic coating, wherein the organic coating is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyimide, acrylonitrile-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, acrylic acid-styrene copolymer, polydimethylsiloxane, sodium polyacrylate, and sodium carboxymethyl cellulose, and the inorganic coating is selected from at least one of SiO2, Al2O3, CaO, TiO2, ZnO2, MgO, ZrO2, and SnO2.
[0068] The present application has no particular limitation on the shape and thickness of the separator. The method for preparing the separator is a method for preparing a separator that can be used in an electrochemical device and is well known in the art.
[0069] [case]
[0070] In some embodiments, the positive electrode sheet, the isolation membrane and the negative electrode sheet are stacked in order so that the isolation membrane is between the positive electrode sheet and the negative electrode sheet, and then a wound battery cell (or electrode assembly) is obtained by winding. The battery cell is placed in a shell and injected with electrolyte. After vacuum packaging, standing, formation, shaping, capacity division and other processes, an electrochemical device can be obtained.
[0071] In other embodiments, the battery cells are stacked.
[0072] In other embodiments, the electrochemical device is used in conjunction with a circuit protection board.
[0073] The housing is a hard shell housing or a flexible shell. The material of the hard shell is, for example, metal. The flexible shell is, for example, a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0074] (Electronic Devices)
[0075] The present application also provides an electronic device including the above-mentioned electrochemical device. The electronic device of the present application is any electronic device, such as but not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. It is noted that the electrochemical device of the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. Air vehicles include air vehicles within the atmosphere and air vehicles outside the atmosphere.
[0076] [test]
[0077] Some specific examples and comparative examples are listed below to better illustrate the present application. In the following examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0078] The lithium ion batteries of Examples 1-1 to 1-37, Examples 2-1 to 2-12, Examples 3-1 to 3-2 and Comparative Examples 1-1 to 1-6 were all prepared according to the following method:
[0079] (1) Preparation of positive electrode sheet
[0080] The positive electrode materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), and Super-P were dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 96:2:2 and mixed evenly to form a positive electrode slurry. The positive electrode slurry was evenly coated on a positive electrode current collector aluminum foil with a thickness of 12μm, baked at 120℃ for 1h, and then compacted and cut to obtain a positive electrode sheet.
[0081] (2) Preparation of negative electrode sheet
[0082] A negative electrode active material with no protective layer or with a protective layer on the surface, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber are dissolved in water at a mass ratio of 85:2:13, and the mixture is fully mixed and stirred to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on a negative electrode current collector copper foil with a thickness of 12 μm, and the negative electrode film is obtained by baking at 120° C. for 1 h. The negative electrode sheet is then obtained by compacting and cutting, wherein the negative electrode active material is a mixed material of a silicon-based active material (SiO) and graphite.
[0083] (3) Preparation of isolation membrane
[0084] A single-layer PE porous polymer film is used as the isolation membrane, with a thickness of 5 microns and a porosity of 40%. The inorganic coating is Al2O3, and the organic particles are polyvinylidene fluoride.
[0085] (4) Preparation of electrolyte
[0086] The first substance, the second substance and the third substance are mixed in a certain proportion to obtain an electrolyte, such as in Example 1, the mass proportion of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether is 40%, and the mass proportion of ethylene glycol diethyl ether and lithium bis(fluorosulfonyl)imide in the electrolyte is 60%, or other additives in different contents are further added to the above electrolyte, such as in Example 2-2, on the basis of the electrolyte in Example 1-7, 5% of fluoroethylene carbonate is added to the electrolyte.
[0087] (5) Preparation of lithium-ion batteries
[0088] A 12μm polypropylene film is used as a separator. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound into a square bare cell. The bare cell is placed in an aluminum foil packaging bag, baked at 80°C to remove water, and a dry cell is obtained. The corresponding electrolyte is injected, and after vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.
[0089] According to the above method, lithium ion batteries of Examples 1-1 to 1-37, Examples 2-1 to 2-12, Examples 3-1 to 3-2 and Comparative Examples 1-1 to 1-6 were prepared, and the battery performance was tested. In Examples 1-1 to 1-37, Examples 2-1 to 2-12, Examples 3-1 to 3-2 and Comparative Examples 1-1 to 1-6, the types and contents of the substances or additives used, the parameters of the silicon-based material surface protective layer, and the performance test results of the lithium ion batteries are shown in Tables 1 to 3, wherein the content of each additive is the weight percentage calculated based on the mass of the electrolyte.
[0090] Next, the performance of the lithium-ion battery was tested.
[0091] (1) High temperature cycle performance test
[0092] The battery was charged to 4.45V at a constant current of 0.5C at 45°C, left for 30 minutes, and discharged to 3.0V at 0.5C, and the charge and discharge cycle was repeated 300 times.
[0093] Cycle capacity retention rate (%) = 300 discharge capacity / first discharge capacity × 100%.
[0094] (2) Normal temperature cycle performance test
[0095] The battery was charged to 4.45V at a constant current of 0.5C at 25°C, left for 30 minutes, and discharged to 3.0V at 0.5C, and the charge and discharge cycle was repeated 300 times.
[0096] Cycle capacity retention rate (%) = 300 discharge capacity / first discharge capacity × 100%.
[0097] The electrical performance test data are as follows:
[0098] In Table 1, the negative electrode material is a mixture of silicon-based material and graphite, wherein the silicon-based material accounts for 65% of the negative electrode active material, and there is no protective layer on the surface of the silicon-based material. Comparative Example 1-1 uses a traditional carbonate electrolyte as a control, and the formula is as follows: ethylene carbonate: diethyl carbonate are mixed evenly in a ratio of 3:7 to obtain a basic solvent, and LiPF6 is dissolved in the above-mentioned basic solvent to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of LiPF6 is 12.5wt%;
[0099] Table 1 Parameters of Examples 1-1 to 1-37 and Comparative Examples 1-1 to 1-6
[0100]
[0101]
[0102]
[0103]
[0104] In Table 1, the conventional solvent + lithium salt electrolyte is used in Comparative Example 1-1, and the cycle decay is rapid; in Examples 1-1 to 1-6, the content of the first substance is controlled to be 40%, and the weight ratio of the second substance to the third substance is adjusted to be between 1.7-4, and the cycle performance is significantly improved compared with Comparative Examples 1-1, Comparative Examples 1-2, and Comparative Examples 1-3; the value of Y is preferably 0.8-4. When the Y ratio is too small, it is easy to cause the third substance to be unable to completely dissolve in the second substance, and the electrolyte will be obviously turbid or precipitated, as shown in Comparative Example 1-2, and the electrical performance test cannot be performed. In contrast, when the Y value is too large, as shown in Comparative Example 1-3, due to the low content of the third substance, the second substance and the third substance cannot form an ideal solvent coordination, and the cycle performance of the corresponding electrochemical device is affected.
[0105] In Examples 1-7 to 1-11, when the content of the first substance in the electrolyte is between 15% and 80%, the performance of the electrochemical device is improved to varying degrees. When the content of the first substance is too low, it cannot effectively participate in the film-forming reaction at the electrode interface, affecting the cycle performance of the electrochemical device. When the content of the first substance is too high, the kinetic performance of the electrolyte is affected, and the effect of improving the performance of the electrochemical device is not significant.
[0106] It can be seen from Examples 1-1 to 1-37 and Comparative Examples 1-1 to 1-6 that by adding the first substance, the second substance and the third substance to the electrolyte and adjusting the types and contents of the first substance, the second substance and the third substance, the electrochemical device can have significantly improved cycle performance.
[0107] In Table 2, the negative electrode material is a mixture of silicon-based material and graphite, wherein the silicon-based material accounts for 65% of the negative electrode active material, and there is no protective layer on the surface of the silicon-based material.
[0108] In Examples 2-1 to 2-12, except for adding additives to the electrolyte, other preparation processes and parameters are the same as those of Example 17. The types and contents of the added additives are shown in Table 2.
[0109] Table 2 Parameters of Examples 1-7 and Examples 2-1 to 2-12
[0110]
[0111]
[0112] It can be seen from Examples 1-7 and Examples 2-1 to 2-12 in Table 2 that by adding other film-forming additives such as fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, adiponitrile, 1,3,6-hexanetrinitrile or hexynenitrile to the electrolyte, the formation and repair of the CEI film and the SEI film can be assisted, and the cycle performance of the electrochemical device can be further improved. Each additive can be added separately or used in combination.
[0113] In Examples 3-1 and 3-2, except that a protective layer is provided on the surface of the silicon-based material, the rest of the preparation process and parameters are the same as those of Example 2-11. The types of the protective layer are shown in Table 3.
[0114] Table 3 Parameters of Examples 2-11, 3-1 and 3-2
[0115]
[0116] In Table 3, the silicon-based material used in Example 2-11 is not surface treated, and the carbon coating layer and the oxide protective layer are respectively provided on the surface of the silicon-based material in Examples 3-1 and 3-2. It can be seen that by providing a protective layer on the surface of the silicon-based material, the expansion of the silicon-based material can be suppressed and the cycle stability of the battery can be further improved.
[0117] The above disclosed features are not intended to limit the scope of implementation of the present disclosure. Therefore, all equivalent changes made to the contents described in the claims of the present disclosure should be included in the scope of the claims of the present disclosure.
Claims
1. An electrochemical device comprising a negative electrode sheet and an electrolyte, The negative electrode plate comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; The electrolyte contains a first substance, a second substance and a third substance; The first substance is selected from a fluorobenzene compound or a fluoroether compound; The second substance is selected from at least one of phosphates, phosphites, carbonates, carboxylates, ethers or sulfones; The third substance is a lithium salt; Based on the mass of the electrolyte, the mass ratio of the second substance to the third substance is Y, and the range of Y is: 0.8≤Y≤4; The fluorobenzene compound is selected from at least one of fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene or hexafluorobenzene; The structural formula of the fluoroether compound is the compound shown in Formula 1, in, R1 and R2 are independently selected from substituted or unsubstituted C 1-12 Alkyl, C 1-12 Alkoxy; wherein, when substituted, the substituent is fluorine, and there are at least 4 fluorines in Formula 1.
2. The electrochemical device according to claim 1, wherein: The fluoroether compound is selected from methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,1,2,2-pentafluoro-3-(trifluoromethoxy)propane, 1,1,1,2,2,3,3-heptafluoro-3-methoxypropane, ethyl 1,1,2,3,3,3-hexafluoropropyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,1,2,3,3-hexafluoro-3-methoxypropane, 2,2,3,3,3-pentafluoropropyl-1,1,2, At least one of 2-tetrafluoroethyl ester, methyl 2,2,3,3,3-pentafluoropropyl ether, 2,2,3,3-tetrafluoro-1-methoxypropane, 2,2,3,3,3-pentafluoropropyl difluoromethyl ether, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 4-(difluoromethoxy)-1,1,1,2,3,3-hexafluorobutane, 2H-hexafluoropropyl 2,2,3,3-tetrafluoroether or 1-(1,1,2,2-tetrafluoroethoxy)butane.
3. The electrochemical device according to claim 1, wherein The mass ratio of the first substance to the electrolyte is A%, and 15≤A≤80.
4. The electrochemical device according to claim 1, wherein The second substance is selected from at least one of the following substances: Triethyl phosphite, trimethyl phosphite, triethyl phosphate, trimethyl phosphate, tripropyl phosphate, triphenyl phosphate, tris(trifluoroethyl) phosphate, tris(trimethylsilyl) phosphate, trimethylsilyl phosphite, Bis(2,2,2-trifluoroethyl) carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dipropyl carbonate, methylpropyl carbonate, pentafluoropropyl ethylene carbonate, methyl trifluoroethyl carbonate, trifluoromethyl ethylene carbonate, Propyl propionate, ethyl propionate, ethyl acetate, ethyl formate, methyl acetate, propyl acetate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl propionate, methyl trifluoropropionate, Ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, 1,3-dioxane, 1,4-dioxane, ethylene glycol formic acid ethyl ether, diethoxymethane, 1,3-dimethoxypropane, 1,1,3,3-tetraethoxypropane, 18-crown-6, 12-crown-4, 15-crown-5, Sulfolane, dimethyl sulfone.
5. The electrochemical device according to claim 1, wherein The third substance is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorooxalatoborate) or lithium 4,5-dicyano-2-(trifluoromethyl)imidazole.
6. The electrochemical device according to claim 1, wherein The electrolyte further comprises an additive; The additive is at least one selected from fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, 1,4-butane sultone, 2,4-butane sultone, succinonitrile, adiponitrile, fumaronitrile, glutaronitrile, 1,3,6-hexanetrinitrile, 1,2,3-tris(2-cyano)propane or acetylene nitrile; The mass proportion of the additive in the electrolyte is B%, and 0.5≤B≤30.
7. The electrochemical device according to claim 1, wherein: Based on the total weight of the negative electrode active material, the mass percentage of the silicon-based material is a%, and 10≤a≤90.
8. The electrochemical device according to claim 1, wherein The surface of the silicon-based material particles has a protective layer; the protective layer includes graphite carbon material and / or functional oxide; The chemical formula of the functional oxide is Me m O n , wherein Me includes at least one of Al, silicon, Mn, V, Cr, Co or Zr, m is 1 to 2, and n is 1 to 3.
9. An electronic device comprising the electrochemical device according to any one of claims 1 to 8.
Citation Information
Patent Citations
Lithium ion battery electrolyte suitably used for silicon-carbon negative electrode
CN105470563A
Electrochemical device and electronic device
CN113921909A